2002
DOI: 10.2308/aud.2002.21.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Misstatements on Decisions of Financial Statement Users: An Experimental Investigation of Auditor Materiality Thresholds

Abstract: Auditors are faced with the dilemma of inferring materiality based, in part, on whether a given level of financial misstatement will affect the decisions of statement users. Misstatements in accounting information that are below the materiality threshold are not expected to change users' assessments of a company's economic condition. While the auditing profession accepts materiality in concept, its application in practice is more controversial. In certain settings, the nature of a misstatement, such as changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
1
21
0
2
Order By: Relevance
“…omissions, errors in estimations), such that many studies and standard setters recommend using thresholds to define the relevance of such misstatements (e.g. AASB, 2009;ESMA, 2011;Mio and Fasan, 2013;Lydenberg, 2012;Tuttle et al, 2002), in which case the magnitude of misstatements becomes the guide for implementing materiality. Other scholars (e.g.…”
Section: Concept Of Materiality In Corporate Reportingmentioning
confidence: 99%
“…omissions, errors in estimations), such that many studies and standard setters recommend using thresholds to define the relevance of such misstatements (e.g. AASB, 2009;ESMA, 2011;Mio and Fasan, 2013;Lydenberg, 2012;Tuttle et al, 2002), in which case the magnitude of misstatements becomes the guide for implementing materiality. Other scholars (e.g.…”
Section: Concept Of Materiality In Corporate Reportingmentioning
confidence: 99%
“…Specifically, they find that investors use a lower level of materiality than those used in practice and suggested in pedagogical literature. Further, Tuttle et al (2002) find that nonprofessional investors do not trade according to standard, quantitative thresholds of materiality employed by auditors.…”
Section: How Materiality Is Determinedmentioning
confidence: 96%
“…With the exceptions of Cho et al (2003), Haka et al (1986), Fisher (1990) and Tuttle et al (2002), the majority of the existing materiality research has overwhelmingly focused on the auditor's perspective (e.g., Ward, 1976;Moriarity and Barron, 1979;Steinbart, 1987;Chewning et al, 1989;Morris and Nichols, 1988). While important to investigate and understand, some problems can occur when considering materiality from the auditor's perspective.…”
Section: How Materiality Is Determinedmentioning
confidence: 98%
“…This material information must be disclosed or the statements would be considered false or misleading. Tuttle et al (2002) reported that market prices are actually overstated when material misstatements are not corrected in the fi nancial statements. Whether an item is material varies according to the particular business or industry, and situation, resulting in a subjective concept.…”
Section: Introductionmentioning
confidence: 97%